2012
DOI: 10.1002/jtr.1909
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation in Tourism at a World Heritage Site: Mutianyu Great Wall, Beijing, China

Abstract: Community participation is crucial for successful heritage tourism and community development. Levels and ways of participation vary, depending on nature and context of heritage sites. This paper explores community participation in tourism at Mutianyu Great Wall, China. General positive perceptions toward World Heritage, tourism development and tourism impacts are held by different groups of the local community. Between-group differences indicate that local opinions are influenced by different levels of impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 19 publications
1
73
1
7
Order By: Relevance
“…Su and Wall [13] investigated community participation in tourism at a World Heritage Site at Mutianyu Great Wall, China. They found that residents have positive perceptions towards World Heritage, tourism development and tourism economic, social, cultural and environmental impacts.…”
Section: Residents' Attitudes Toward Tourism Development In World Hermentioning
confidence: 99%
See 1 more Smart Citation
“…Su and Wall [13] investigated community participation in tourism at a World Heritage Site at Mutianyu Great Wall, China. They found that residents have positive perceptions towards World Heritage, tourism development and tourism economic, social, cultural and environmental impacts.…”
Section: Residents' Attitudes Toward Tourism Development In World Hermentioning
confidence: 99%
“…There have been a number of studies focused on local residents' attitudes in World Heritage Sites [4][5][6][7][8][9][10][11][12][13][14], but there has not been any research dealing with local residents' attitudes towards different forms of tourism development (CTD and SITD). Therefore, this paper could be potentially valuable for those researchers who explore local residents' attitudes toward special interest tourism development generally and in World Heritage Sites.…”
Section: Introductionmentioning
confidence: 99%
“…The WHS-embodied cultural and natural values were propitious to tourism development [25]; ecotourism can be a major force in sustainable development of the WHS [26], and also helped to improve local residents' livelihood. Therefore, tourism can effectively promote WHS sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, a central aspect of the marketing of heritage regions concerns trying to achieve a balance in terms of generating commercial activity and preserving the heritage region Gilmore, Carson, Ascenção and Fawcett, 2008;Jones and Shaw, 2012). This involves making a decision regarding whether to actively market a region as a tourist destination, which will have an impact on the social and environmental nature of the region (Su and Wall, 2014). There will be considerations in terms of allowing and developing access to heritage resources, given the need to offer a range of tourist products and services.…”
Section: Heritage Tourism Marketing Planningmentioning
confidence: 99%